The Role of Business in Global Sustainability Transformations - D'Amato, Dalia; Toppinen, Anne; Kozak, Robert (Routledge Research in Sustainability and Business, 2023)
Drawing on contributions from more than thirty scholars and experts in the field, this book examines the role of business as an enabler, as an inhibitor, and ultimately as a co-actor in global sustainability transformations expected over the next few decades. The Role of Business in Global Sustainability Transformations employs several theoretical perspectives and provides abundant examples and cases to discuss a variety of emerging concepts, phenomena, and trends shaping business sustainability. Weaving through the chapters, the editors present core tensions and sources of inertia towards transformative change, and acknowledge that envisioning multiple solutions and pathways are possible and desirable. They advocate for the need to align visions, actions and time horizons between policy, society and business in addressing the interlinked socio-ecological challenges that our society currently faces. This book will be an important resource for scholars and professionals working in the field of sustainability and sustainable business, and a vital educational text for students interested in this discipline.